A Tungsten Chloride Free, One‐Step Hydrothermal Method to Synthesize P25/Blue WO3‐x Heterostructures. Issue 29 (1st August 2022) - Zhang, Zhiguang; Zhou, Fang; Yu, Guifeng; Long, Yunze; Wang, Qiang; Huang, Shulai; Wang, Juan; Yuan, Shuli; Wang, Zhihua
Abstract: Low‐cost and high efficiency P25 (nanoparticles TiO2 )/blue anoxic tungsten oxide (WO3‐x ) heterostructure was successfully constructed by one‐step low‐temperature hydrothermal method. Moreover, sodium tungstate dihydrate (Na2 WO4  ⋅ 2H2 O) instead of tungsten hexachloride (WCl6 ) further lowers cost and facilitates preparation. P25/blue WO3‐x heterostructure, rich in oxygen vacancies with typical blue color, exhibits improved performances in both electrocatalysis and photocatalysis. Compared with the pure P25 and blue WO3‐x, the exchange current density of P25/blue WO3‐x was increased by 6 times and 22 times, respectively. P25/blue WO3‐x showed the lowest over potential and relatively small Tafel slope. Also, the degradation efficiency of P25/blue WO3‐x was much higher than other samples. The mechanism of photocatalysis was investigated. The trapping experiments confirmed h + and ⋅OH were the main active species in photocatalytic reaction. The matched energy levels and built‐in electric field of heterostructure interface can inhibit the recombination of photogenerated electron‐hole pairs to enhance the photodegrading efficiency. The simple low‐cost method is a beneficial attempt to prepare excellent bi‐functional materials with electrocatalytic and photocatalytic properties for practical application prospect in energy shortage and environmental pollution. Abstract : P25 (nanoparticles TiO2 )/blue WO3‐x heterostructure was constructed by a simple one‐step low‐temperature hydrothermal method. Moreover, sodium tungstate dehydrate instead of tungsten hexachloride further lowers cost and facilitates preparation. P25/blue WO3‐x heterostructure showed excellent properties of photodegradition and hydrogen evolution reaction. The bi‐catalytic properties with high efficiencies imply an expected practical application prospect. The mechanisms of enhanced electrocatalytic and photocatalytic properties of P25/blue WO3‐x heterostructure were demonstrated.